Studies On Therapeutic Efficacy Of Fresh And Stored Blood Transfusion In Clinically Anaemic Canines - Kumar, Anil; Haque , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
25 clinically anemic canines randomly divided into 5 equal groups were studied. Group T5 was treated as control group, T1 was transfused with fresh blood and T2, T3, and T4 with 7, 14 and 21 day preserved blood respectively. The hematology showed significant decrease in hemoglobin, PCV, total erythrocyte count and mean corpuscular hemoglobin concentration. But on 24, 72 and 120 hours post blood transfusion, a significant increase in the hematological parameters approaching to normal values were observed; where as no significant improvement was noticed in anemic control group treated with single i.m iron dextran injection.
Keywords: anorexia; anemia; blood transfusion; hemoglobin and packed cell volume